A comparative evaluation of efficiency of fixed combination hypotensives for the treatment of primary open-angle glaucoma - F. A. Bakhritdinova; S. Sh. Mirrakhimova; U. R. Karimov; A. . Khera (Российский офтальмологический журнал, 2018)
Purpose. To compare hypotensive efficiency and safety of fixed combinations of drugs treating primary open-angle glaucoma (POAG). Material and methods. We conducted a randomized prospective clinical trial which involved 80 patients (158 eyes) divided into 4 groups) and lasted six months. The patients received timolol 0.5 % + travoprost 0.004 % (group1), timolol 0.5 % + brimonidine 0.2 % (group 2), timolol 0.5 %+brinzolamide 1 % (group 3) and timolol 0.5 % + pilocarpin 2 % (group 4). Results. All fixed drug combinations compared were found to produce a hypotensive effect in the treatment of POAG patients. Over 6 months, IOP dropped by 20.6 % to 33.1 % against the initial level. The best and the longest-lasting effect was achieved when the first combination, timolol+travoprost (jointly called duotrav), was used. Conclusion. The Duotrav combination should be prescribed for long-term treatment of POAG and ocular hypertension. Timolol + brimonidine and timolol + brinzolamide are the most effective in short-term therapy of POAG and ocular hypertension, as well as in the pre-operative period prior to surgeries of glaucoma with high IOP. After normal IOP values have been obtained, the patient should be prescribed Duotrav, which is a more stable combination. Travoprost 0.004 %/timolol with 0.5 % is more effective, stabile and safe combination and recommend for long-term therapy of. Even though the combination of timolol and pilocarpin is not generally recommended for POAG therapy, it can be used for short-term inexpensive POAG and ocular hypertension treatment // Russian Ophthalmological Journal, 2016; 4: 5-10. doi: 10.21516/2072-0076-2016-9-4-5-10.